2010
DOI: 10.3354/cr00899
|View full text |Cite
|
Sign up to set email alerts
|

Estimating changes in Scottish soil carbon stocks using ECOSSE. I. Model description and uncertainties

Abstract: To predict the response of C-rich soils to external change, models are needed that accurately reflect the conditions of these soils. Estimation of Carbon in Organic Soils -Sequestration and Emissions (ECOSSE) is a model that allows simulations of soil C and N turnover in both mineral and organic soils using only the limited meteorological, land-use and soil data that is available at the national scale. Because it is able to function at field as well as national scales if appropriate input data are used, field-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 37 publications
1
104
0
Order By: Relevance
“…Future model development should ensure a dynamic coupling of soil organic carbon content and soil thermal and hydraulic properties (Falloon et al, 2011), as well as allowing for sub-grid variability and uncertainty in soil properties. A separate peat module for JULES is already under development in order to study peatland carbon dynamics in the boreal zone, and work is underway to couple JULES to a more advanced model of carbon and nitrogen turnover in both mineral and organic soils (Smith et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Future model development should ensure a dynamic coupling of soil organic carbon content and soil thermal and hydraulic properties (Falloon et al, 2011), as well as allowing for sub-grid variability and uncertainty in soil properties. A separate peat module for JULES is already under development in order to study peatland carbon dynamics in the boreal zone, and work is underway to couple JULES to a more advanced model of carbon and nitrogen turnover in both mineral and organic soils (Smith et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is, therefore, considerable research activity in predicting changes in soil carbon in response to land-use change (e.g. ECOSSE; Smith et al, 2007c), but this knowledge is not yet at a stage at which it can be incorporated into the national inventory for the UK. The potential advantages in decreasing net carbon emissions of changing land use from arable to grass are thus challenging to estimate at the farm level, and cannot yet be captured in the metrics used by policy-makers.…”
Section: Gill Smith and Wilkinsonmentioning
confidence: 99%
“…There were only small differences in the organic C contents of organic layers under forestry compared to semi-natural soils, with some horizons having greater organic C contents in afforested compared with semi-natural soils, and other horizons showing the opposite trend (Smith et al 2010b). Therefore, no adjustment was made to the C contents of the soil horizons of uncultivated soils to distinguish between afforested soils and those under semi-natural vegetation.…”
Section: Input Data Used To Drive the Simulationsmentioning
confidence: 99%
“…Because it is able to function at both field and national scales, if the model is driven by appropriate input data, field-scale evaluations can be used to determine uncertainty in national simulations. In an evaluation of uncertainty in simulations driven only by the limited data available at a national scale, Smith et al (2010b) concluded that simulated values show a high degree of association with the measurements in both total C and change in C content of the soil. Over all sites where land-use change occurred, the average deviation between the simulated and the measured values of percentage change in soil C was less than the experimental error (11% simulation error, 53% measurement error), suggesting that the uncertainty in the national-scale simulations is ~11%.…”
mentioning
confidence: 99%
See 1 more Smart Citation